2021
DOI: 10.1111/nmo.14161
|View full text |Cite
|
Sign up to set email alerts
|

Examining the optimal cutoff values of HADS, PHQ‐9 and GAD‐7 as screening instruments for depression and anxiety in irritable bowel syndrome

Abstract: Background: Self-rating scales are frequently used to screen for anxiety and depression in patients with irritable bowel syndrome (IBS). Different cutoff values are recommended in literature, and guidelines have suggested the use of other screening instruments over time. The aim of this study was to assess the correlation between the most commonly used psychological screening instruments for anxiety and depression in IBS and to compare custom cutoff scores for these instruments. Methods: Irritable bowel syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 36 publications
2
36
0
1
Order By: Relevance
“…A strong correlation was found for mean daily stress during the week as determined using ESM and both GAD-7 total scores and HADS-D scores (Pearson r of 0.906 and 0.717, respectively) in patients with FD (Table 2). When using cutoff values of 8 for HADS-D and 10 for GAD-7 to screen for depressive and anxiety disorder in a group of patients with a functional GI disorder (30), 5 of 35 patients with FD scored positive for a possible depressive disorder and 5 of 35 patients with FD scored positive for a possible anxiety disorder.…”
Section: Resultsmentioning
confidence: 99%
“…A strong correlation was found for mean daily stress during the week as determined using ESM and both GAD-7 total scores and HADS-D scores (Pearson r of 0.906 and 0.717, respectively) in patients with FD (Table 2). When using cutoff values of 8 for HADS-D and 10 for GAD-7 to screen for depressive and anxiety disorder in a group of patients with a functional GI disorder (30), 5 of 35 patients with FD scored positive for a possible depressive disorder and 5 of 35 patients with FD scored positive for a possible anxiety disorder.…”
Section: Resultsmentioning
confidence: 99%
“…There is no single generally accepted cut-off score for the Hospital Anxiety Depression (HAD), although Zigmond and Snaith suggested 7/8 for possible and 10/11 for probable anxiety or depression and we have always chosen to use a value of 10 or above in our previous studies. Some authors have suggested slightly lower cut-off values, 24 but these have not been universally accepted. Consequently, to allow comparison with our previous work, we have continued to use a cut-off of 10 in this study.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, our study population consisted of referrals form tertiary care, where a higher prevalence of psychological co‐morbidities can exist 32 . Comparing our results with a larger and more recent study that included primary and secondary/tertiary care patients with IBS, the prevalence of depression was 20% and anxiety was 26% when using a HADS cut‐off ≥8 33 . In another tertiary care setting, anxiety was 45% and depression was 26% in IBS patients when using a HADS cut‐off ≥8 11 .…”
Section: Discussionmentioning
confidence: 65%
“…32 Comparing our results with a larger and more recent study that included primary and secondary/tertiary care patients with IBS, the prevalence of depression was 20% and anxiety was 26% when using a HADS cut-off ≥8. 33 In another tertiary care setting, anxiety was 45% and depression was 26% in IBS patients when using a HADS cut-off ≥8. 11 Considering the rates observed in the present study, we can say our tertiary care population is similar to others, although it does not represent the general IBS population.…”
Section: Psychological Outcomesmentioning
confidence: 98%